Pengaruh Enterprise Risk Manajement terhadap Nilai Perusahaan dengan Variabel Kontrol: Ukuran Perusahaan dan DER: Effect of Enterprise Risk Management on Firm Value with Control Variables: Firm Size and DER - Murtini, Umi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2018)
This study aimed to examine the effect of Enterprise Risk Management (ERM) to the firm value with control variables comprising firm size and FER. The method used is Weighted Least Square (WLS) with the error term as variable weights. The research sample are manufacturing companies registered in the Indonesia Stock Exchange in the period 2011-2015. The results showed that the ERM effect on the firm value with firm size as control variables.